Macroalgae Sargassum cristaefolium Extract Inhibits Proinflammatory Cytokine Expression in BALB/C Mice - Eka Sunarwidhi Prasedya; Ni Wayan Riyani Martyasari; Angga Susmana Abidin; Sonia Ardilla Pebriani; Bq Tri Khairina Ilhami; Andri Frediansyah; Anggit Listyacahyani Sunarwidhi; Sri Widyastuti; Haji Sunarpi (Scientifica)
Ultraviolet radiation (UVR) which could induce skin damage and skin disease is a growing concern due to the increase in global warming. Brown macroalgae Sargassum cristaefolium has been recognized to exhibit UV protective activities. However, the mechanism of its photoprotective activity remains unclear. The purpose of this study is to investigate the potential mechanism of S. cristaefolium’s photoprotective activity against UV radiation. Phytochemical analyses revealed valuable bioactive compounds in SCE, such as fucoxanthin which is widely known as an anti-inflammatory carotenoid. Treatment with SCE before UV-A radiation show reduced levels of wrinkles and desquamation. Interestingly, SCE treatment induces the skin healing process after UV radiation. SCE effectively inhibited proinflammatory TNF-α and IL-6 expression while increasing IL-10 production in the BALB/c mice skin. Current results suggest that SCE potentially protects the skin by attenuation of inflammatory cytokines. In addition, SCE demonstrates promising antibacterial activity (MIC = 1.302 µg/mL) against Staphylococcus aureus. Overall, SCE could be a source of an effective anti-inflammatory agent protecting against UV irradiation-induced skin damages.